Wide-angle color holographic near eye display with full bandwidth frequency multiplexing - Maksymilian Chlipala; Maria-Luisa Cruz; Juan Martinez-Carranza; Moncy Idicula; Rafal Kukolowicz; Tomasz Kozacki (Scientific Reports)
Abstract Wide-angle holographic near-eye displays (HNEDs) face challenges in achieving high frame rates, full-color, high-resolution images, and shallow depth of field. Existing full-color methods either rely on time multiplexing or suffer from reduced image resolution due to the applied filtering of the available spatial bandwidth of the light modulator. To address these limitations, we propose a non-pupil HNED system that reconstructs large 3D full-color scenes from a single hologram using RGB LED illumination. The non-pupil architecture allows employing an incoherent LED source, which offers reduced speckle noise and high imaging resolution. This is, to our knowledge, the first wide-angle 3D color holographic display to use a single spatial light modulator (SLM) at full frame rate. Our system is supported by a developed computer generation hologram (CGH) method, which maximizes the SLM’s bandwidth for color coding and improves the speed of RGB CGH calculations. Additionally, we introduce a frequency filter design to simplify color coding and illumination alignment. Through optical reconstructions, we demonstrate that our method preserves 3D depth and color distribution, achieving high-resolution color holographic video without compromising refresh rate or hologram bandwidth.